10 National study on the risks of COVID-19 for paediatric renal transplant recipients. (15th December 2021) - Withers, Charlotte; Reynolds, Ben; Christian, Martin; Muorah, Mordi; Tse, Yincent; Edwards, Liz; Yadav, Pallavi; Haq, Shuman; Hedge, Shivaram; Marks, Stephen
Abstract : Introduction: From the start of the COVID-19 pandemic, evidence emerged that children were less affected by SARS-CoV-2 PCR DNA COVID-19 positive infections, with increasing evidence showing immunosuppressed children were less at risk compared to immunosuppressed adults. The aim of our study was to investigate how COVID-19 infections affected paediatric renal transplant recipients in the UK. Methods: Questionnaires regarding patient demographics, renal transplant information, COVID-19 infection data and care of patients during the COVID-19 pandemic were sent out to all 13 UK paediatric nephrology centres. Results: 54 patients (69% male; 50% Black, Asian and minority ethnic [BAME]; 57% living donors) aged 4–19 (median 11) years and between 2 months – 15 years (median 3 years 1 month) post-transplantation from nine centres tested positive for SARS-CoV-2 PCR DNA. Four centres had no positive patients. 48% presented with the classical COVID-19 symptoms (37% fever, 11% continuous cough and 4% loss of sense of taste or smell); atypical presentations included diarrhoea (13%) and headache (8%). 37% of patients were asymptomatic. 28% were hospitalised (median stay 2 days) which included asymptomatic patients admitted for other reasons. Of those admitted, one patient required oxygen; however, no patients required ventilation or intensive care admission. One child had a rejection episode as a complication of the infection and one adolescent had ongoing cardiorespiratory symptoms for six months. There was evidence of AKI with renal transplant dysfunction in 31% of patients, with increase in mean baseline plasma creatinine from 80.6µmol/l to 171.7µmol/l, but no patients required CVVH or dialysis. Conclusion: 9% of the UK paediatric renal transplantation population have had documented SARS-CoV-2 PCR DNA infections with 28% required hospitalisation. There was increased prevalence of AKI, particularly after the first wave of the COVID-19 pandemic, possibly due to different variants, although there is no specific virological data to support this.